A stress-control charging method with multi-stage currents for silicon-based lithium-ion batteries: Theoretical analysis and experimental validation. (1st December 2022) - Zhang, Kai; Zhou, Junwu; Yang, Fuhao; Zhang, Yuwei; Pan, Yihui; Zheng, Bailin; Li, Yong; Yang, Fuqian
Abstract: Controlling mechanical stress in silicon-based anode has been proved to be an effective method in improving the cycling performance of silicon-based lithium-ion battery. This work is aimed at developing stress-control charging strategies from the stress analysis of a silicon particle. Using a mechanochemical model coupled with the free volume theory, we analyze the stress evolution in a silicon particle with multi-stage current strategies for a small charging rate (C-rate) at a low SOC and a large C-rate at a high SOC . The calculation results support the proposed strategies in reducing the stresses in the silicon particle. We perform experimental tests, including cycling test and SEM (scanning electron microscopy) analysis, and demonstrate the feasibility of the proposed strategies. Using multi-stage currents for lithiation and a constant current for delithiation can have a conspicuous effect on improving the cycling performance of silicon-based lithium-ion batteries. Highlights: Stress evolutions in amorphous silicon anodes guide to develop charging methods. Charging protocols with multi-stage currents for lithiation are proposed. The validity of proposed protocols of improving cycling performances is verified.